Experiences following cataract surgery – patient perspectives. (11th July 2020) - Webber, Kathryn J; Fylan, Fiona; Wood, Joanne M; Elliott, David B
Abstract: Purpose: Most patients report being highly satisfied with the outcome of cataract surgery but there are variable reports regarding the impact of cataract surgery on some real‐world activities, such as fall rates. We hypothesised that adaptations to changed refractive correction and visual function may cause difficulties in undertaking everyday activities for some patients and used a series of focus groups to explore this issue. Method: Qualitative methods were used to explore patients' experiences of their vision following cataract surgery, including adaptation to vision changes and their post‐surgical spectacle prescription. Twenty‐six participants took part in five focus groups (Mean age = 68.2 ± 11.4 years), and the data were analysed using thematic analysis. Results: We identified three themes. 'Changes to Vision' explores participants' adaptation following cataract surgery. While several had problems with tasks relying on binocular vision, few found them bothersome and they resolved following second eye surgery. Participants described a trial and error approach to solving these problems rather than applying solutions suggested by their eyecare professionals. 'Prescription Restrictions' describes the long‐term vision problems that pre‐surgery myopic patients experienced as a consequence of becoming emmetropic following surgery and thus needing spectacles for reading and other close work activities, which they did not need before surgery. Very few reported that they had the information or time to make a decision regarding their post‐operative correction. 'Information Needs' describes participant's responses to the post‐surgical information they were given, and the unmet information need regarding when they can drive following surgery. Conclusion: The findings highlight the need for clinicians to provide information on adaptation effects, assist patients to select the refractive outcome that best suits their lifestyle, and provide clear advice about when patients can start driving again. Patients need to be provided with better guidance from clinicians and prescribing guidelines for clinicians would be beneficial, particularly for the period between first‐ and second‐eye surgery.